Showrooms of intimacy in the internet: images to keep or to show? - Sibilia, Paula (2011)
There are many similarities between the analog family photographs, which still survive at home in drawers, albums and shelves, and the new digital images, which are increasingly available online. However the disparities among them are also important and provocative. This article aims to highlight the contrasts, indicating some aspects, which suggest the preservation of intimate archives to be substituted by the wish to show – and perhaps then discarding – this kind of images.